Hematite iron oxide nanoparticles: apoptosis of myoblast cancer cells and their arithmetical assessment. Issue 44 (9th July 2018) - Wahab, Rizwan; Khan, Farheen; Al-Khedhairy, Abdulaziz A.
Abstract : Hematite (α-Fe2 O3 ) forms iron oxide nanoparticles (NPs) which are thermally stable and have various electrochemical and optochemical applications. Abstract : Hematite (α-Fe2 O3 ) forms iron oxide nanoparticles (NPs) which are thermally stable and have various electrochemical and optochemical applications. Due to their wide applicability, the present work was designed to form the hematite phase of iron oxide (αFe2 O3 NPs) NPs prepared via a solution process. Their cytological performance was checked with C2C12 cells. The crystalline property of the NPs was examined with X-ray diffraction patterns (XRD) and it was found that the size of the particles formed ranged from 12 to 15 nm. Structural information was also identified via field emission scanning electron microscopy (FESEM) and transmission electron microscopy (TEM), which again confirmed that the size of each NP is about 12–15 nm. Surface topographical analysis was done via atomic force microscopy (AFM), which reveals that the size of the distance between two particles is in the range of 12 ± 3 nm. The C2C12 cells were cultured in a humidified environment with 5% CO2 and were checked via a microscope. The αFe2 O3 NPs were used for cytotoxic evaluation against C2C12 cells. A MTT (3-(4, 5-dimethyl thiazol-2-yl)-2, 5-diphenyltetrazolium bromide) assay was utilized to check the viability of cells in a dose-dependent (100 ng mL −1, 500 ng mL −1 or 1000 ng mL −1 ) manner. The morphology of the cells under the influence of αFe2 O3 NPs for live and dead cells in a wet environment was confirmed via confocal laser scanning microscopy (CLSM). The apoptosis caused due to the αFe2 O3 NPs was evaluated in presence of caspases 3/7 with GAPDH genes, which confirmed the upregulation that is responsible in caspase 3/7 genes, with treatment of C2C12 at low (500 ng mL −1 ) and high (1000 ng mL −1 ) doses of αFe2 O3 NPs. Analytical studies were also performed to authenticate the obtained data for αFe2 O3 NPs using parameters such as precision, accuracy, linearity, limits of detection (LOD) and limit of quantitation (LOQ), quantitative recoveries and relative standard deviation (RSD). The analyses play a significant role in investigating the large effect of αFe2 O3 NPs on C2C12 cells.